The global shock in economic activities: Covid-19 pandemonium - Chinenye Ifeoma Nwokolo; Matthew Ikechukwu Ogbuagu; Onyebuchi Iwegbu (BizEcons Quarterly, 2020)
The sudden outbreak of coronavirus disease (COVID-19) has become a global pandemic as the number of deaths at about 3, 400 with more than 100,000 confirmed cases as of March 7, 2020, have suddenly upshot to 192,166 deaths and over 2.7 million cases as of April 24, 2020. This alarming rate of spread poses a challenge to leaders, economist, and policymakers in the world and have distrust global economic activities. COVID-19 has caused public health emergency and significant global economic shock which cuts across all sectors, resulting simultaneously into demand and supply shocks. Among suggested policy measures include reduction of interest rates as low as the 2009 subprime crisis percentage point just to encourage investment and recovery in global activities, intensification of surveillance by local and international health organisations, outbreak readiness, biomedical counter-measures, massive education and enlightenment about the virus using all local dialects focused on the mode of transmission and preventive measure. For the implementation of these policy solutions, maximum support is needed from all stakeholders such as the governments and non-governmental organizations, health professionals, community leaders and the citizens at large.
Keywords: E30; G01; G02; 330; Global Shock; Economic Activities; Covid-19